2021
DOI: 10.1177/10790632211002858
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Latent Structure of Dynamic Risk: Seeking Empirical Constraints on Theory Development Using the VRS-SO and the Theory of Dynamic Risk

Abstract: The present study is part of a larger project aiming to more closely integrate theory with empirical research into dynamic risk. It seeks to generate empirical findings with the dynamic risk factors contained in the Violence Risk Scale—Sexual Offense version (VRS-SO) that might constrain and guide the further development of Thornton’s theoretical model of dynamic risk. Two key issues for theory development are (a) whether the structure of pretreatment dynamic risk factors is the same as the structure of the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Moreover, D7 emotional control loaded on Sexual Deviance while D17 intimacy deficits loaded on Criminality; this makes some sense, however. For instance, Olver et al (2022) found D7 emotional control loaded significantly on Sexual Deviance on the combined four samples making up the norms for the VRS-SO, but at a magnitude lower than other items with more evident conceptual links (e.g., sexually deviant lifestyle, sexual compulsivity). One possible explanation could be the emotional and coping needs that motivate and are fulfilled by sexual activity, including illegal or paraphilic activities, may account for the connection between this item and the substantive Sexual Deviance factor items.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, D7 emotional control loaded on Sexual Deviance while D17 intimacy deficits loaded on Criminality; this makes some sense, however. For instance, Olver et al (2022) found D7 emotional control loaded significantly on Sexual Deviance on the combined four samples making up the norms for the VRS-SO, but at a magnitude lower than other items with more evident conceptual links (e.g., sexually deviant lifestyle, sexual compulsivity). One possible explanation could be the emotional and coping needs that motivate and are fulfilled by sexual activity, including illegal or paraphilic activities, may account for the connection between this item and the substantive Sexual Deviance factor items.…”
Section: Discussionmentioning
confidence: 93%
“…Our sense on the other third factor, Treatment Responsivity, may have been penalized by incomplete information available from file for coding, given that D15 treatment compliance had to be omitted in almost all instances and could not be reliably scored, followed by D11 released to HRS, which could be rated more frequently but still had missing data. The end result is a factor that is prorated based on item averages and the scores of the two out of four items that could be consistently reliably scored, but missing two items that have demonstrated strong predictive properties in past research (Olver et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic risk factors with strong causal interrelations group together, forming a community of risk factors (van den Berg et al, 2022). Based on previous findings, the NBM-RSR includes communities of dynamic risk factors relevant to sexual self-regulation, (ability to establish and maintain) emotionally intimate relationships, antisociality, and general self-regulation (Figure 5; Brouillette-Alarie et al, 2016; Hanson & Morton-Bourgon, 2005; Malamuth, 1986; Malamuth, 2003; Malamuth & Hald, 2016; Malamuth et al, 1995; Olver et al, 2021; Stinson & Becker, 2013; Stinson et al, 2016; Stinson et al, 2008; Thornton, 2002; Thornton, 2013; van den Berg et al, 2020; van den Berg et al, 2022). In contrast with Thornton’s SRA model (2002, 2013), in which pro-offending attitudes are a separate domain, within the NBM-RSR these attitudes form a dynamic risk factor together with other risk-relevant behavioral and psychological features and are part of one of the four communities.…”
Section: Network-based Model Of Risk Of Sexual Reoffending (Nbm-rsr)mentioning
confidence: 99%
“…Risk assessments may inform charging and sentencing decisions, the availability and intensity of treatment services offered, whether or when to release, conditions for supervision in the community, or even removal from “sexual offender” registries (Thornton et al, 2021). Contemporary instruments for assessing sexual recidivism risk are largely focused on static and dynamic risk factors (e.g., Brankley et al, 2021; Helmus, Thornton et al, 2012), both of which can be regarded as indexing the operation of long-term vulnerabilities for offending (Olver et al, 2021; Thornton, 2016; Ward & Beech, 2004).…”
mentioning
confidence: 99%